Combined inhibition of 20-hydroxyeicosatetraenoic acid formation and of epoxyeicosatrienoic acids degradation attenuates hypertension and hypertension-induced end-organ damage in Ren-2 transgenic rats - Čertíková-Chábová, Věra; Walkowska, Agnieszka; Kompanowska-Jezierska, Elzbieta; Sadowski, Janusz; Kujal, Petr; Vernerová, Zdenka; Vaňourková, Zdeňka; Kopkan, Libor; Kramer, Herbert J; Falck, John R; Imig, John D; Hammock, Bruce D; et al. (Clinical science (1979), 2010)
Recent studies have shown that the renal CYP450 (cytochrome P450) metabolites of AA (arachidonic acid), the vasoconstrictor 20-HETE (20-hydroxyeicosatetraenoic acid) and the vasodilator EETs (epoxyeicosatrienoic acids), play an important role in the pathophysiology of AngII (angiotensin II)-dependent forms of hypertension and the associated target organ damage. The present studies were performed in Ren-2 renin transgenic rats (TGR) to evaluate the effects of chronic selective inhibition of 20-HETE formation or elevation of the level of EETs, alone or in combination, on the course of hypertension and hypertension-associated end-organ damage. Both young (30 days of age) prehypertensive TGR and adult (190 days of age) TGR with established hypertension were examined. Normotensive HanSD (Hannover Sprague-Dawley) rats served as controls. The rats were treated with N-methylsulfonyl-12,12-dibromododec-11-enamide to inhibit 20-HETE formation and/or with N-cyclohexyl-N-dodecyl urea to inhibit soluble epoxide hydrolase and prevent degradation of EETs. Inhibition in TGR of 20-HETE formation combined with enhanced bioavailability of EETs attenuated the development of hypertension, cardiac hypertrophy, proteinuria, glomerular hypertrophy and sclerosis as well as renal tubulointerstitial injury. This was also associated with attenuation of the responsiveness of the systemic and renal vascular beds to AngII without modifying their responses to noradrenaline (norepinephrine). Our findings suggest that altered production and/or action of 20-HETE and EETs plays a permissive role in the development of hypertension and hypertension-associated end-organ damage in this model of AngII-dependent hypertension. This information provides a basis for a search for new therapeutic approaches for the treatment of hypertension.
Keywords: Animals; hypertenze; angiotensin II; Hydroxyeicosatetraenoic Acids; Amides; multiorgánové selhání; sulfony; kyseliny hydroxyeikosatetraenové; amidy; noradrenalin; Sulfones; renální oběh; Drug Evaluation, Preclinical; krevní tlak; Rats, Sprague-Dawley; preklinické hodnocení léčiv; kyselina 8,11,14-eikosatrienová; Hypertension; Male; potkani Sprague-Dawley; Renal Circulation; Vasoconstrictor Agents; Rats, Transgenic; 8,11,14-Eicosatrienoic Acid; krysa rodu Rattus; vazokonstriktory; Antihypertensive Agents; zvířata; mužské pohlaví; antihypertenziva; Blood Pressure; Rats; potkani transgenní; Norepinephrine; Angiotensin II; Multiple Organ Failure